Synthesis and Crystal Structure Analysis of Histone Deacetylase Inhibitor Chidamide - Bo Han; Xin-Yan Peng; Yan-Qing Gong; Jia-Liang Zhong; Qing-Wei Zhang (Georg Thieme Verlag KG, 2023)
Abstract Chidamide is the first oral subtype-selective histone deacetylase inhibitor approved in China for the treatment of relapsed and refractory peripheral T cell lymphoma. Due to the existence of isomers, many articles or patents have mistaken its structure. Herein we explored the synthesis of the key intermediate (E)-4-((3-(pyridin-3-yl)acrylamido)methyl)benzoic acid (A-3) and chidamide, using the condensing agent HBTU, instead of the unstable N,N'-carbonyldiimidazole. The single crystal of chidamide was determined by X-ray diffraction study. The optimized preparation process was easy to operate, and the purity of the final product can be up to 99.76%. Moreover, the structure of chidamide was established to be (E)-N-(2-amino-4-fluorophenyl)-4-((3-(pyridin-3-yl)acrylamido)methyl)benzamide.